Flora - Flora (Elsevier, 2026)
FLORA, the scientific botanical journal with the longest uninterrupted publication sequence (since 1818), considers manuscripts in a range of areas of botany which appeal to a broad international scientific readership. The journal publishes original contributions and review articles on plant structure (morphology and anatomy), plant developmental biology (ontogeny), phytogeography (including phylogeography), plant population genetics, plant functional ecology (including ecophysiology), plant population ecology, biotic interactions between plants and other organisms, plant community ecology, and ecosystem ecology. Suggestions for Special Issues are welcome, as are compilations of manuscripts (both original and review articles) for Special Features on a specific topic.
FI 0.33
Q3
Keywords: Life Sciences; Ecology & Organismal Biology; Ecología; Biología de los organismos; Acuerdos transformativos; Transformative agreements; Fitogeografía; Poblaciones vegetales; Ontogenia; Ecología de ecosistemas